L. V. Shchyhlo. Development of word-formation processes in the german language. - L. V. Shchyhlo (Philological Treatises, 2020)
The article is devoted to the development of word-formation processes in the German language. The main attention of the author is focused on the study of the origin, semantics and historical dynamics of word-formation means at various stages of diachrony of the German language. Significant role in the study of the mechanisms of self-regulation of the word-forming system as an open non-equilibrium non-linear system is played by synergetics as a theory of self-organization, which is aimed at the discovery of universal laws of evolution. The application of the principles and methods of the synergetic methodology for solving the problems of word formation opens up new horizons in the study of the word-formation system as a whole and its subsystems in particular. Description of the morphological structure of the word from the standpoint of evolutionary linguistic synergetics contributes to the “unpacking” (term by T. I. Dombrovan) of the word, revealing the complex nature of a simple word.